Os caminhos de uma nova siembra petrolera: distribuição e circulação da renda petroleira na Venezuela Bolivariana (2003-2012) - Ribeiro, Vicente Neves da Silva (2018)
The following work analyzes the distribution of oil rents in the period from 2003 to2012, in Venezuela. This period owes its specificity to a favorable environment for oil prices in the international market; a new regulatory framework for the oil sector aimedat increasing tax revenues; a closer government control over the national oil company,Petróleos de Venezuela, S.A. (PDVSA), and the beginning of currency exchange con-trol. The understanding of how this period of Bolivarian Venezuela is inserted in thewider history of Venezuela as an oil exporting country is sought, analyzing the mecha-nisms of distribution of oil rents. Firstly, theories of rent of land are discussed, pointingout parameters for the analysis of the oil rents. Secondly, the history of Venezuela as anoil exporting country is brought to discussion, in order to situate the period of analysis in a broader context. Following, some measurements of the oil rents are observed in anattempt to measure it during the studied period. In the end, the most recent history ofVenezuela is placed within a broader picture. This agenda promotes a reflection on themost important mechanisms for the distribution of oil rents during the aforementionedperiod, among which we highlight the importance taken by the PDVSA in the manage-ment of social policies, the role of currency exchange in the transfer of payment capac-ity of the export sector to the import sector and the increasing subsidy to oil products in the domestic market.